Role of Lymphocyte-Monocyte Ratio in predicting the prognosis and outcome of patients with Acute Ischemic Stroke - Fabin, Mohammed; Shanker, Swathy; Govind, Bimal; Maliyekkal, Joji (International Clinical Neuroscience Journal, 2025)
Background: Acute ischemic stroke is a sudden disruption in blood flow to the brain, leading to neuronal damage that occurs secondary to inflammation. The outcome depends on the type of stroke, the duration of treatment, and the patient's physical status. Lymphocyte-to-monocyte ratio (LMR) is an emerging biomarker that can predict stroke severity and functional outcome in AIS patients. Methods: This was a prospective, observational study including cases of ischemic stroke presenting to a tertiary care center in Kerala. Patients with neurological symptoms were evaluated according to the NIHSS score, and blood samples were sent for analysis. Patients who presented to the emergency department from July 2024 to December 2024 were included in the study, and a total of 126 patients were observed Results: This study shows that the NIHSS score used to grade stroke severity at admission was negatively associated with LMR values. This shows that lower LMR values are associated with greater stroke severity. A cutoff value of 2.9 was used for this study, and it showed high accuracy. The result of the Spearman correlation showed that there was a very high, negative correlation between LMR and NIHSS Score. The results showed that this correlation between LMR and NIHSS Score was a statistically significant negative correlation, r(124) = -0.71, p = <.001. Conclusion: LMR can be used as an important and effective biomarker in evaluating the severity of the disease and in predicting the outcome in patients with acute ischemic stroke.